Service Quality Assurance and Customer Satisfaction - Bharti Rawat Fonia; Diksha Srivastava (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2023)
The perception of the concept quality has evolved over the years. The service researchers emphasize the importance of studying customer perceived quality since the customers are the only ones entitled to decide what quality is. Service quality is evaluated by means of a comparison of what the customers expect with the service that is delivered. Keywords: Service Quality, Customer Satisfaction, Redressal, Retailing.